2014
DOI: 10.1021/jm500308c
|View full text |Cite
|
Sign up to set email alerts
|

SAR Studies on Curcumin’s Pro-inflammatory Targets: Discovery of Prenylated Pyrazolocurcuminoids as Potent and Selective Novel Inhibitors of 5-Lipoxygenase

Abstract: The anticarcinogenic and anti-inflammatory properties of curcumin have been extensively investigated, identifying prostaglandin E2 synthase (mPGES)-1 and 5-lipoxygenase (5-LO), key enzymes linking inflammation with cancer, as high affinity targets. A comparative structure-activity study revealed three modifications dissecting mPGES-1/5-LO inhibition, namely (i) truncation of the acidic, enolized dicarbonyl moiety and/or replacement by pyrazole, (ii) hydrogenation of the interaryl linker, and (iii) (dihydro)pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Considering the involvement of inflammation in brain ischemic episodes and the anti-inflammatory property of curcumin, as well as its antioxidant activity observed even at lower doses, as shown by us 14 and others,42, 52, 53, 54 our data emphasize the potential benefit of curcumin in the prevention or treatment of stroke.…”
Section: Resultssupporting
confidence: 73%
“…Considering the involvement of inflammation in brain ischemic episodes and the anti-inflammatory property of curcumin, as well as its antioxidant activity observed even at lower doses, as shown by us 14 and others,42, 52, 53, 54 our data emphasize the potential benefit of curcumin in the prevention or treatment of stroke.…”
Section: Resultssupporting
confidence: 73%
“…[8][9][10][11][24][25][26][27] It has received extensive attention with its unique effectiveness in glioma therapy. Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Eicosanoids were analyzed by multiple reaction monitoring. The parameters were adjusted as described . Automatic peak integration was performed with Analyst software version 1.6 (AB Sciex, Darmstadt, Germany) using IntelliQuan default settings.…”
Section: Methodsmentioning
confidence: 99%